From Exclusive to Inclusive A Systematic Review of Hybrid Talent Management Systems - Aditya Santoso; Nasrulloh (Yayasan pendidikan dzurriyatul Quran, 2026)
The concept of talent management has generated substantial debate in the human resource management literature, particularly regarding the question of who should be considered as “talent”. Two competing perspectives exist: the exclusionary approach, which views talent as a limited elite group of high-performing or high-potential workers, and the inclusive individual approach, which assumes that all employees possess talents that can be developed. This study aims to mediate these perspectives through a narrative literature review focusing on influential and highly cited scientific publications, and offering new insights that serve as theoretical foundations for researchers over a period of five years or more. The findings demonstrate a clear shift in the current literature toward a hybrid talent management model that integrates inclusive development systems with strategic differentiation mechanisms. Rather than viewing talent as a fixed attribute, contemporary studies increasingly conceptualize talent as dynamic, context-dependent, and developable. This review reaffirms the hybrid approach to defining talent, which is considered more contextual, balanced, productive, and ethical. It is hoped that the results of this study will free talent management researchers from the trap of the exclusionary-inclusive dichotomy that persists today.